2012
DOI: 10.1111/j.1464-410x.2012.11557.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERG protein, a prostate cancer specific marker, in high grade prostatic intraepithelial neoplasia (HGPIN): lack of utility to stratify cancer risks associated with HGPIN

Abstract: E 7 5 1What ' s known on the subject? and What does the study add? High grade prostatic intraepithelial neoplasia is a pre-malignant lesion to prostate cancer and is associated with 20% -25% risk of prostate cancer in subsequent repeat biopsies. ERG is a highly prostate-cancer-specifi c marker.Expression of ERG is rare in isolated high grade prostatic intraepithelial neoplasia diagnosed in prostate biopsy and is not associated with cancer risk in subsequent repeat biopsies. OBJECTIVES• To evaluate how often ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Nevertheless, both studies demonstrate higher incidence of cancer after ERG-positive HGPIN. He et al 25 had a cohort of 94 patients with biopsies with isolated HGPIN in which only five patients (5.3%) were ERG positive; no differences were observed in subsequent PCa detection between ERG-positive and ERG-negative patients, but the small study size and few number of ERG-positive patients limit interpretation of these results. From the perspective of a randomized, systemically controlled clinical trial with more than 1,500 patients, our results support that patients with ERG-positive HGPIN are more likely to develop PCa than those with ERG-negative HGPIN.…”
Section: Erg Gene Fusion In High-grade Prostatic Intraepithelial Neopmentioning
confidence: 99%
“…Nevertheless, both studies demonstrate higher incidence of cancer after ERG-positive HGPIN. He et al 25 had a cohort of 94 patients with biopsies with isolated HGPIN in which only five patients (5.3%) were ERG positive; no differences were observed in subsequent PCa detection between ERG-positive and ERG-negative patients, but the small study size and few number of ERG-positive patients limit interpretation of these results. From the perspective of a randomized, systemically controlled clinical trial with more than 1,500 patients, our results support that patients with ERG-positive HGPIN are more likely to develop PCa than those with ERG-negative HGPIN.…”
Section: Erg Gene Fusion In High-grade Prostatic Intraepithelial Neopmentioning
confidence: 99%
“…Generally, studies of cancer-adjacent specimens have shown higher rates of ERG expression: 13%–52% 1114,16,17. Studies performed on isolated HGPIN have found ERG expression that was lower or even absent: 0–5% 15,38…”
Section: Discussionmentioning
confidence: 99%
“…25 TMPRSS2:ERG gene rearrangement was found to be highly specific for and present in about 50% of prostate cancers and 29% of foci of PIN, according to immunohistochemical staining with anti-ERG antibody that was highly correlated with TMPRSS2:ERG gene rearrangement status. 29 Conversely, He and colleagues 30 found 38% risk of cancer on repeat biopsy that was independent of ERG staining status with PIN. 27 In a prospective study of ERG staining of biopsies with PIN, Gao and colleagues 28 found that this marker was highly predictive of cancer on repeat biopsy (95% in positive cases vs 5% in negative cases).…”
Section: And Atrophymentioning
confidence: 99%